144 A Clinical Practice Assessment In Tardive Dyskinesia: Are Physicians Up-to-Date?. (15th June 2018) - Lubarda, Jovana; Hughes, Stacey; Correll, Christoph U.
Abstract: Study Objectives: To assess physicians' current knowledge, skills, competence, and practice barriers regarding tardive dyskinesia (TD) and assess continuing medical education (CME) needs. Assessment Methods: A 29-question clinical practice assessment survey instrument consisting of multiple-choice knowledge and case-based questions was administered online to gather abaseline "snapshot" of knowledge, skills, attitudes, and competence on TD epidemiology, risk factors, diagnosis, current guideline-based management, and emerging management strategies The survey launched online on a website dedicated to continuous professional development on July 25, 2016, and was made available to healthcare providers without monetary compensation or charge. Data were collected through August 28, 2016 Confidentiality was maintained and responses were de-identified and aggregated prior to analyses Results: Data were collected for the 1157 psychiatrists and 177 neurologists who responded to all survey questions during the study period. The findings were: ∙ Epidemiology: 62% of psychiatrists and 68% of neurologists were aware that TD affects approximately 20% of patients treated with neuroleptic agents ∙ Risk factors: 63% of psychiatrists and 67% of neurologists were aware of risk factors for TD, such as older age ∙ Diagnosis: 93% of psychiatrists and 71% of neurologists were aware that Abnormal Involuntary Movement Scale (AIMS) can be used to support diagnosis of TD ∙ Guidelines: 21% of psychiatrists and 11% of neurologists were aware of the American Psychiatric Association guidelines for monitoring of TD, and 56% of psychiatrists and 42% of neurologists were aware of the American Academy of Neurology guidelines on treatment of TD New/emerging treatments: 24% of psychiatrists and 34% of neurologists were aware of the mechanisms of action of new/emerging treatments for TD, and 54% and 44%, respectively, were aware of the clinical data for valbenazine Conclusions: This educational research yielded important insights into clinical practice gaps in TD, indicating that both psychiatrists and neurologists would benefit from continuing medical education on epidemiology, risk factors, diagnosis, guideline-based care, and information on how to incorporate new/emerging treatments for TD into practice. Funding Acknowledgements: The educational activity and outcomes measurement were funded through an independent educational grant from Neurocrine Biosciences, Inc.